ANALISIS BELANJA DAERAH KOTA BAUBAU - Sarnani, Sarnani (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2022)
This study aims to determine the factors that affect Regional Expenditures. This research will be carried out in Bau-bau City in April 2018 until it is completed. At the office of the regional financial and property management agency (BPKBMD). The results of this study indicate that from the results of partial coefficient testing (t test) it can be concluded that: (1). the explanatory variable of Regional Original Income (X1) with regional expenditure in the city of Bau-bau has no significant effect, which means that it does not match the hypothesis. This variable describes the role of PAD in financing regional expenditures in each region where expenditure consists of direct expenditure and indirect expenditure. Where PAD experienced a decline in regional spending by -10,809. (2). The Balanced Funds variable (X2) with regional expenditures in the city of Baubau has no significant effect, which means that it does not match the hypothesis. A 1% increase in Balancing Funds in each Baubau City regional expenditure will cause an increase in regional spending in each region of 3,181 t-testers prove that the t-statistical value is in the H0 receiving area, meaning that the independent variable balancing funds has no significant effect on the City's regional expenditure variable.